Eficacia del Mindfulness en el Tratamiento para el Consumo de Sustancias en Adultos: Revisión Sistemática - Balcázar Espinoza., Nayeli Andrea (2024)
Mindfulness is a relevant component of third generation therapies. It is based on intentionally paying attention to the present moment without judgment. It has scientific evidence to address various mental disorders including substance abuse which refers to the fact of introducing drugs into the body, which produce alterations and changes in behavior and is currently a public health problem. Despite the availability of various treatments, not all patients obtain satisfactory results, thus the need to study other approaches such as mindfulness. The scarcity of studies in this field and the increase in the number of people who use substances reinforce this need. The purpose of this study was to describe the scientific evidence of the efficacy of mindfulness in the treatment of substance abuse in adults by identifying the most commonly used mindfulness-based intervention and determining the sociodemographic characteristics of people with this pathology. The study was conducted with a quantitative approach, non-experimental, cross-sectional and descriptive design. A bibliographic synthesis was developed using the PRISMA method with scientific literature from databases such as: PubMed, ScienceDirect, Redalyc and PubPsych, selection criteria were applied to form a sample of 18 scientific articles. The results indicated the efficacy of mindfulness in reducing substance use, increasing abstinence, reducing relapse and better management of craving. Mindfulness-based Relapse Prevention was identified as the most widely used mindfulnessbased intervention. Within the sociodemographic characteristics, a higher prevalence of male gender, white ethnicity and the most consumed substance was alcohol. Based on these results, an informative guide was elaborated with the aim of psychoeducating the population on the subject